Penerapan Teknologi Informasi Untuk Meningkatkan Efisiensi Oprasional Umkm Di Madura Dari Persepektif Ekonomi Syariah - salman Alfarisi; M Shofi Saputra; Arisa Qurrotu Aini Lina; Abdur Rohman (BISMA : Business and Management Journal, 2025)
The development of information technology has opened up new opportunities for Micro, Small, and Medium Enterprises (MSMEs) in increasing operational efficiency and business competitiveness. In the Madura region, the MSME digitalization process cannot be separated from the strong socio-religious context, where sharia economic values also influence the pattern of technology adaptation. This study aims to examine the implementation of information technology in MSMEs in Madura, with a focus on the integration of sharia economic principles in the digitalization process. The research approach used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation of MSMEs in various sectors. The results of the study show that the use of technology by MSMEs in Madura has helped increase operational efficiency, especially in terms of communication, promotion, and transaction recording. On the other hand, business actors continue to maintain business practices that are in line with Islamic values, such as honesty, transparency, and avoidance of usury practices. However, obstacles are still found in the form of low digital literacy, limited infrastructure, and minimal ongoing assistance which cause digitalization to not run optimally. Therefore, a supporting strategy is needed in the form of contextual training, an integrated and simple technology system, and strengthening the digital ecosystem based on sharia communities. This finding shows that digitalization and sharia values are not two contradictory things, but can strengthen each other in the development of sustainable and ethical MSMEs.